Tumor suppressive functions of WNT5A in rhabdomyosarcoma - Ragab, Nada; Bauer, Julia; Uhmann, Anja; Marx, Alexander; Hahn, Heidi; Simon-Keller, Katja (International journal of oncology, 2022)
Rhabdomyosarcoma (RMS) is a highly aggressive soft tissue malignancy that predominantly affects children. The main subtypes are alveolar RMS (ARMS) and embryonal RMS (ERMS) and the two show an impaired muscle differentiation phenotype. One pathway involved in muscle differentiation is WNT signaling. However, the role of this pathway in RMS is far from clear. Our recent data showed that the canonical WNT/β‑Catenin pathway serves a subordinate role in RMS, whereas non‑canonical WNT signaling probably is more important for this tumor entity. The present study investigated the role of WNT5A, which is the major ligand of non‑canonical WNT signaling, in ERMS and ARMS. Gene expression analysis showed that WNT5A was expressed in human RMS samples and that its expression is more pronounced in ERMS. When stably overexpressed in RMS cell lines, WNT5A decreased proliferation and migration of the cells as demonstrated by BrdU incorporation and Transwell migration or scratch assay, respectively. WNT5A also decreased the self‑renewal capacity and the expression of stem cell markers and modulates the levels of muscle differentiation markers as shown by sphere assay and western blot analysis, respectively. Finally, overexpression of WNT5A can destabilize active β‑Catenin of RMS cells. A WNT5A knockdown has opposite effects. Together, the results suggest that WNT5A has tumor suppressive functions in RMS, which accompanies downregulation of β‑Catenin.